STEAM Education Using Design Thinking Process Through Virtual Communities of Practice (STEAM-DT-VCoPs) - Thiti Jantakun; Kitsadaporn Jantakun; Thada Jantakoon (Journal of Educational Issues, 2024)
These objectives of the study are 1) to design STEAM education using Design Thinking Process through Virtual Communities of Practice (STEAM-DT-VCoPs), and 2) to evaluate the designed STEAM-DT-VCoPs. It divides the research procedures into two phases. The first phase is to design STEAM-DT-VCoPs, and the second phase is to evaluate the STEAM-DT-VCoPs. The sample group of this study comprises fourteen experts selected by purposive sampling. The arithmetic mean and standard deviation analyzed data. The research findings are: 1) The STEAM-DT-VCoPs comprise three steps are 1.1) the role of virtual communities of STEAM practice 1.2) Design Thinking Process through Virtual Communities of Practice, and 1.3) the various disciplines in STEAM education. 2) The experts agree that STEAM-DT-VCoPs is the highest level of appropriateness.